Empowering Odheng Artisans through Strengthening Entrepreneurship and Branding of Traditional Products in West Pademawu - Ismi Fitri Aulia; Mohammad Faris; Subhan Subhan; Rika Syahadatina; Alfi Hasaniyah; Devi Lestari Pramita Putri; Jamilatul Badriyah (Jurnal Pengabdian Masyarakat Al-Fatimah, 2025)
Odheng craftsmanship is a distinctive cultural heritage of Madura that continues to be preserved; however, it faces significant challenges in the modern era, particularly in terms of business management and marketing. In West Pademawu Village, Pamekasan Regency, most artisans still operate their businesses conventionally, lacking adequate knowledge of entrepreneurship and product branding strategies. This community service program aims to empower odheng artisans by strengthening their entrepreneurial capacity and developing product branding. The implementation method consists of three stages: preparation, implementation, and evaluation. Activities were carried out participatively through counseling, training, and direct mentoring approaches. The results show an increase in participants' motivation and understanding related to business management and basic financial recordkeeping. Furthermore, the artisans have begun to utilize digital platforms such as Instagram, Facebook, and marketplaces (Shopee, TikTok Shop) for product promotion and sales. Evaluation was conducted through online monitoring and indicated that the targets for participation, skills improvement, and sustainability were significantly achieved. This program demonstrates that training- and mentoring-based interventions can enhance the competitiveness of local products and promote community economic independence. Through the integration of local and digital approaches, odheng product branding has been successfully improved, transforming it not only into a cultural symbol but also into a valuable economic commodity